2017
DOI: 10.1155/2017/9614241
|View full text |Cite
|
Sign up to set email alerts
|

Review of Routine Laboratory Monitoring for Patients with Rheumatoid Arthritis Receiving Biologic or Nonbiologic DMARDs

Abstract: Safety concerns associated with many drugs indicated for the treatment of rheumatoid arthritis (RA) can be attenuated by the early identification of toxicity through routine laboratory monitoring; however, a comprehensive review of the recommended monitoring guidelines for the different available RA therapies is currently unavailable. The aim of this review is to summarize the current guidelines for laboratory monitoring in patients with RA and to provide an overview of the laboratory abnormality profiles asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 87 publications
1
19
0
3
Order By: Relevance
“…In RA patients, NLR has been reported to be a good indicator of response to tocilizumab treatment [23]. In a review of the treatment effect on laboratory parameters in Rigby et al in RA patients, they concluded that all treatments, including biological agents, reduced serum neutrophil and platelet levels [24]. Koiwa et al emphasized that NLR shows efficacy of biological treatments but is not a predictor of biological agent treatment [25].…”
Section: Discussionmentioning
confidence: 99%
“…In RA patients, NLR has been reported to be a good indicator of response to tocilizumab treatment [23]. In a review of the treatment effect on laboratory parameters in Rigby et al in RA patients, they concluded that all treatments, including biological agents, reduced serum neutrophil and platelet levels [24]. Koiwa et al emphasized that NLR shows efficacy of biological treatments but is not a predictor of biological agent treatment [25].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are two JAKi approved for RA treatment, associated with MTX or as monotherapy: tofacitinib (selective for JAK1 and JAK3) and baricitinib (selective for JAK1 and JAK2). Also, other agents are undergoing clinical studies: upadacitinib and filgotinib (selective for JAK1, 74-fold selectivity for the first agent and 28-fold for the second one), peficitinib (selective for JAK1 and JAK2) and decernotinib (JAK3 selective) [124][125][126][127].…”
Section: Type 2 Receptors Include Il-10 and Tnf Familiesmentioning
confidence: 99%
“…As well as baricitinib, it should be used carefully in patients with risk factors for deep vein thrombosis (DVT) or pulmonary embolism (PE) (old age, obesity, history of DVT or PE, surgery or immobilization). It is not recommended in case of pregnancy, lactation or children; it is also important to administer with caution in patients over 75 years [127]. Baricitinib, the second agent approved for the treatment of RA is a competitive ATP kinase inhibitor, selective inhibitor of JAK1 and JAK2 (100-fold selectivity over JAK3), that reduces immune cell functions by targeting several cytokines (IL-6, IL-12, IL-23, IFNs, and GM-CSF) and growth factor stimulation.…”
Section: Baricitinibmentioning
confidence: 99%
See 2 more Smart Citations